(untitled) (London Journal of Medical and Health Research, 2023)
Background: When COVID-19 vaccines arrived in Uganda in March of 2021, there was inadequate information on vaccine acceptance in the population due to many factors, but mainlydue to misinformation and disinformation circulating in Ugandan media. This study aimed to determine the prevalence and factors associated with COVID-19 vaccine acceptance among adult population in northern Uganda. Methods: We conducted a cross-sectional study on 723-adult populations in northern Uganda from March to April of 2022. Participants were selected by systematic sampling from twenty-four health facilities in Acholi sub-region. SPSS version 25.0 was used for data analysis at multivariable regression analysis and a p-value <0.05 was considered significant. Results: COVID-19 vaccine acceptance among adult population (mean age, 31.36 years SD±10.07), (95%CI:30.62-32.10) was high at 580/723(80.2%,95%CI:78.9%-83.4%). Factors associated with vaccine acceptance were likely among participants who strongly disagree (aOR=adjusted Odds Ratio)=3.31,95%CI:1.49-7.36;p=0.003) and disagree (aOR=1.98,95%CI:1.01-3.89;p=0.046) that vaccines in health facilities in northern Uganda were safe than those who strongly agree, respectively; participants from Gulu (aOR=5.19,95%CI:1.71-15.80;p=0.004), Kitgum (aOR=6.05,95%CI:1.76-20.80;p=0.004), and Pader districts(aOR=3.45,95%CI:1.07-11.14;p=0.038)than Lamwo district ,respectively; smokers (aOR=7.75,95%CI:2.06-29.23;p=0.002) than non-smokers; non-health workers (aOR=1.74,95%CI:1.03-2.96;p=0.040) than health workers; females (aOR=1.59,95%CI:1.04-2.42;p=0.032)than males; Baganda tribe (aOR=5.19,95%CI:1.71-15.80;p=0.004); and other tribes (aOR=6.05,95%CI:1.76-20.80;p=0.040) than Itesot, respectively. However, it was less likely for participants with comorbidities (aOR=0.42,95%CI:0.25-0.71;p=0.001); graduates (aOR=0.42,95%CI:0.18-0.99;p=0.049); and age-group of 20-29 years (aOR=0.52,95%CI:0.31-2.96;p=0.040) to accept COVID-19 vaccines. Conclusion: COVID-19 vaccine acceptance among participants from northern Uganda was high. Participants who strongly disagree and disagree that vaccines in northern Uganda’s health facilities were safe; smokers, non-health workers, females, Baganda tribe, and participants from Gulu, Kitgum, and Pader districts were more likely to accept COVID-19 vaccines. However, it was less likely for participants with comorbidities, age-group of 20-29 years, and graduates to accept COVID-19 vaccines. The fear of contracting coronavirus and death if not vaccinated contributed substantially to COVID-19 vaccine acceptance. There is a need to engage, sensitize and mobilize the population on COVID-19 vaccinesusing community health workers such as the village health teams (VHTs).